The role of endogenous sources in the system of good governance of countryside - Káposzta, József (Studia Mundi – Economica, 2018)
We are undergoing such economic changes nowadays, which fundamentally change the world economic circumstances as the previous sources for growth have been exhausted, productive capital declined and consequently the incentives for investment has reduced, furthermore it got worse with the shocking effect of financial crisis. More and more serious tension is accumulated in the economic core area of significant industrial states, partly because of the environmental problems coming to the front and partly due to the crisis of the traditional manufacturing bases, which was further hampered. On the basis of these considerations, the economic development based on endogenous sources can be considered a factor of growing importance and the development of local markets as the local usage of income produced locally has become an unavoidable economic strategy in several fields. The present paper examines this topic regarding its links and tries to find connection for the improvement of good governance.